Smooth speed control of permanent magnet vernier machine using active disturbance rejection control - Tan, Wei Hao (Nanyang Technological University, 2022)
Permanent Magnet Vernier Machines (PMVM) exhibit satisfactory performance characteristics for direct-drive applications, producing high torque at low speeds. However, torque ripples due to manufacturing tolerances deteriorate speed control of the motors at low speeds. Extended State Observer (ESO) based Active Disturbance Rejection Control (ADRC) controllers are preferred as they are Two Degree of Freedom (TDOF) controllers and comparatively simpler among other TDOF controllers. However, the classic ESO-ADRC controller is unable to suppress sinusoidal disturbances, e.g., the torque ripples in question. Hence, in this paper, a Second Order Generalized Integrator (SOGI) equipped ESO-ADRC controller is proposed to enable the controller to suppress the sinusoidal torque ripples, achieving smooth speed control of PMVM at low speeds. Simulations and experiments were conducted to verify the effectiveness of the proposed controller.